Continuous syngas production from CO2 captured by a transition-metal-free dual-function material using a moving-bed reactor - Yuya Ono; Makiko Tokuda; Tomone Sasayama; Fumihiko Kosaka; Shinta Miyazaki; Hiroyuki Takano; Koji Kuramoto (Journal of Environmental Chemical Engineering, 2026)

Protein source and redox-mediated structural modifications, bioactivity, and celiac-related peptides in high-moisture extruded gluten-based meat analogs - Shinta Maharani; Prisana Suwannaporn; Jenshinn Lin; Jue-Liang Hsu (Food Chemistry, 2026)

A new Armorloricus (Loricifera: Nanaloricidae) from the Pacific Ocean and guidelines for describing new species based on Higgins larvae - Shinta Fujimoto; Hiroshi Yamasaki; Motohiro Shimanaga; Hidetaka Nomaki (Marine Biodiversity, 2026)

Correction: Gut microbiota profile, potential engineering techniques and its genetic and epigenetic implications in poultry health - Nuruliarizki Shinta Pandupuspitasari; Sugiharto Sugiharto; Faheem Ahmed Khan; Muhammad Asif Raza; Dela Ayu Lestari; Asep Setiaji; Ikania Agusetyaningsih (World Journal of Microbiology and Biotechnology, 2026)

Innovative Synergy of Circular Economy and Environmental Literacy: Transforming Eco-Tourism for Marine Conservation and Ecosystem Restoration - Suwaib Amiruddin; Asep Marfu; Agung Purwanto; Dwi Atmanto; Achmad Husen; Arita Marini; Heri Sapari Kahpi; Septantri Shinta Wulandari; Anna Sofia Atichasari (Circular Economy and Sustainability, 2026)

Modeling Critical Drivers of Circular Economy Transition Using Fuzzy ISM and Fuzzy MICMAC Analysis - Dwi Atmanto; Asep Marfu; Agung Purwanto; Arita Marini; Nadiroh; Achmad Husen; Heri Sapari Kahpi; Septantri Shinta Wulandari; Anna Sofia Atichasari; Esti Suntari (Circular Economy and Sustainability, 2026)

Spatiotemporal changes in 137Cs concentration in Japanese flounder Paralichthys olivaceus in Sendai Bay and the adjacent area off the coast of Fukushima Prefecture in relation to the dynamic states of 137Cs in the ecosystem - Yutaka Kurita; Yuya Shigenobu; Hiroyuki Togashi; Takami Morita; Shinta Sakurai; Hideki Kaeriyama (Journal of Environmental Radioactivity, 2026)

Revitalizing Ecosystems: The Role of Circular Economy and Energy Accounting Through Waste Utilization and Energy Efficiency - Srie Nuning Mulatsih; Anna Sofia Atichasari; Asep Marfu; Agung Purwanto; Dwi Atmanto; Ahmad Husen; Arita Marini; Suwaib Amiruddin; Heri Sapari Kahpi; Septantri Shinta Wulandari (Circular Economy and Sustainability, 2026)

Hospital Circularity Reimagined: Exploring Interdependent Drivers of Sustainable Transitions - Asep Marfu; Agung Purwanto; Dwi Atmanto; Henita Rahmayanti; Arita Marini; Samlibry Adhitia; Catur Wahyu Prasetyo; Sandhi Prasetiawan; Daiman Daiman; Septantri Shinta Wulandari; Anna Sofia Atichasari; Heri Sapari Kahpi (Circular Economy and Sustainability, 2026)

Harnessing Green Human Resource for Renewable Energy and Material Innovation: A Pathway to Economic Sustainability Through Emission Reduction and Resource Circularity - Nieke Masruchiyah; Novita Damayanti; Prasetya Yoga Santoso; Septantri Shinta Wulandari; Ana Sofia Atichasari; Asep Marfu (Circular Economy and Sustainability, 2026)

A Multi-Method Framework for Prioritizing Circular Economy Drivers in Sustainable Hospitals - Asep Marfu; Agung Purwanto; Dwi Atmanto; Henita Rahmayanti; Arita Marini; Desy Safitri; Vera Julia; Leola Dewiyani; Rezeqi Hardam Saputro; Nindhita Priscillia Muharrani; Septantri Shinta Wulandari; Anna Sofia Atichasari (Circular Economy and Sustainability, 2026)

From Waste to Wealth: How Circular Economy Enhances Social Resilience in Urban Communities Through Recycling Innovation and Public Participation - Asep Marfu; Agung Purwanto; Dwi Atmanto; Nadiroh; Hafid Abbas; Muhammad Zid; Henita Rahmayanti; Arita Marini; Samlibry Adhitia; Catur Wahyu Prasetyo; Sandhi Prasetiawan; Daiman; et al. (Circular Economy and Sustainability, 2026)

Deciphering the potential of flavonols as SARS-CoV-2 MPro inhibitors: an in silico investigation using pass prediction, molecular docking, molecular dynamics simulation and ADMET analysis - Athira E; Jibin K. Varughese; Shinta Davis; Deepthi Jose; Vijisha K. Rajan (In Silico Pharmacology, 2026)

Physiological and Transcriptomic Insights into Mechanisms of Salt Tolerance in the Leaves and Roots of the Halophyte Suaeda japonica Makino Under High Salinity Stress - Shinta; Kristine Mae Y. Bentoy; Anisa Nazera Fauzia; Mami Nampei; Nguyen Manh Linh; Akihiro Ueda (Journal of Plant Growth Regulation, 2026)
Suaeda japonica Makino, a succulent euhalophyte from the Chenopodiaceae family, grows naturally in Japan and is presumed to exhibit high salt tolerance. However, the molecular mechanisms underlying its salinity tolerance remain poorly understood. This study aimed to examine the physiological responses of S. japonica to varying NaCl concentrations, perform transcriptome profiling of its leaves and roots under 600 mM NaCl exposure, and identify key genes involved in salt tolerance. S. japonica exhibited remarkable tolerance to extreme salinity levels of up to 600 mM for 28 days. Physiological analysis revealed that salinity stress led to increased Na + , soluble sugars, and proline; increased antioxidant enzyme activities; and decreased malondialdehyde (MDA) concentrations in the leaves, indicating a protective role for osmotic regulation, reactive oxygen species (ROS) scavenging, and protection of cellular macromolecules in S. japonica under high salinity. De novo RNA-seq analysis detected 8695 and 9424 differentially expressed genes (DEGs) in the leaves and roots, respectively. Salinity-responsive transcription factors including bHLH, AP2-EREBP, bZIP, WRKY, NAC, HSF, and MYB have been identified. Additionally, DEGs related to the ABA signaling pathway, ion channels/transporters, Ca 2+ signaling, aquaporins, ABC transporters, starch and sucrose metabolism, proline biosynthesis, LEA proteins, and ROS scavenging were significantly expressed in both the leaves and roots, suggesting that these may be the major protective mechanisms to high salinity stress in S. japonica . This study provides a new perspective on the molecular mechanisms underlying salinity tolerance in S. japonica and establishes a foundation for future research.

Gut microbiota profile, potential engineering techniques and its genetic and epigenetic implications in poultry health - Nuruliarizki Shinta Pandupuspitasari; Sugiharto Sugiharto; Faheem Ahmed Khan; Muhammad Asif Raza; Dela Ayu Lestari; Asep Setiaji; Ikania Agusetyaningsih (World Journal of Microbiology and Biotechnology, 2025)

Stenotrophomonas sp. strain CK1 volatile organic compounds improved rice growth under saline conditions - Kristine Mae Y. Bentoy; Shinta; Mami Nampei; Akihiro Ueda (Theoretical and Experimental Plant Physiology, 2025)
Plant-bacteria indirect interaction is a naturally occurring phenomenon however many aspects of this interaction remain unclear. In this study, the effects of bacterial inoculation were investigated by tissue culture experiments as indirect application to compare rice growth in saline conditions. Four isolates applied indirectly had 1.5-times greater shoot dry mass of rice under 100 mM NaCl treatment. The isolates were identified using 16S rRNA sequencing, with sequences of type strains from the genus Stenotrophomonas aligned using MEGA11, followed by model testing and phylogenetic tree construction. HS-SPME/GC–MS experiment was performed to identify the microbial volatile organic compounds that possibly contribute to the effect of indirect application. A total of 23 compounds were detected with chemical classifications: benzenoids, alkylbenzenes, esters, thioesters, sulfur compounds, amines, organosilicon, alcohols, diakyl ketone, methyl ketone, sulfides, sulfide thioesters, and ketone sulfones. Ten compounds were selected based on GC peak area. Commercially available counterparts of selected VOCs were indirectly applied using concentrations at 1 mM, 10 mM, 100 mM, and 1 M. Shoot dry weight was greater when rice seedlings were exposed to the commercially purchased 1-Butanol, 2-methyl-, (S)- (2 MB), detected in the HS-SPME/GC–MS of Stenotrophomonas sp. broth culture. Element analysis revealed significantly higher Mn, Fe, Zn shoot concentration in the rice seedlings exposed to 2 MB compared to seedlings grown in 100 mM NaCl without VOC exposure. The seedlings grown in 100 mM NaCl also had lower K, Ca, Mg, P, and Cu shoot element concentrations. Significant relative gene expressions of OsYSL15 , OsNAS1 , OsNAS2, and OsRMC were observed in shoot rice seedlings exposed to 2 MB in saline conditions. Thus, indirect interaction of environmental bacteria can influence plant physiology via microbial volatile organic compounds.

Changes in the coastal environments and their impact on society in the Qaanaaq region, northwestern Greenland - Shin Sugiyama; Atsushi Yamaguchi; Tatsuya Watanabe; Yasumasa Tojo; Naotaka Hayashi; Jean-Baptiste Thiebot; Makoto Tomiyasu; Kohei Hasegawa; Yoko Mitani; Mayuko Otsuki; Yuta Sakuragi; Monica Ogawa; et al. (Polar Science, 2025)

Psychological Factors Influencing Environmental Knowledge and their Impact on Indonesian Circular Economy Adoption - Asep Marfu; Agung Purwanto; Nadiroh; Hafid Abbas; Bagus Sumargo; Septantri Shinta Wulandari; Daiman; Christin A. Malaihollo; Syakyakirti; David Tanubrata; Dewi Indah Pratiwi (Circular Economy and Sustainability, 2025)

Sorption experiments using stemflow: Reproduction and understanding of radiocesium dynamics on the forest floor during the early stage after the Fukushima nuclear accident - Takuya Manaka; Shinta Ohashi; Wataru Sakashita; Naohiro Imamura; Yoshiyuki Inagaki (Journal of Environmental Radioactivity, 2025)

Elucidating the antioxidant potential of some flavanones as MAO-B inhibitors through DAM, in silico molecular docking and computational analysis - E. Athira; S. Akhila Darsan; Shinta Davis; Vijisha K. Rajan (Plant Molecular Biology, 2025)

Ingested microplastics: a comparative analysis of contaminated shellfish from two sites in the Makassar Strait - Shinta Werorilangi; Ega Adhi Wicaksono; Muh. Afdal; Kuasa Sari; Robby Nimzet; Wasir Samad; Ramdha Mawadda; Sulaiman Gosalam; Liestiaty Fachruddin; Arniati Massinai; Ahmad Faizal (Environmental Monitoring and Assessment, 2025)

Influence of ripening stage on the microwave-assisted pectin extraction from banana peels: A feasibility study targeting both the Homogalacturonan and Rhamnogalacturonan-I region - Yujie Mao; Shinta R. Dewi; Stephen E. Harding; Eleanor Binner (Food Chemistry, 2024)

Evaluation of sediment transport estimates using Sediment Routing Analysis (SRA) model: study case of Rawa Pening Lake - Hanggar Ganara Mawandha; M. Eka Bimantara Putra; Issiami Nursafa; Krisnadi Cahyo Yuliardi; Lalu Marhayani Kesuma; Dewi Shinta Rulisyani (Modeling Earth Systems and Environment, 2024)

Kinorhynch fauna from Oki Islands, with the description of a new Echinoderes species and its phylogenetic relationships within the family Echinoderidae - Hiroshi Yamasaki; Masa-aki Yoshida; Naoto Jimi; Natsumi Hookabe; Misato Sako; Hisanori Kohtsuka; Shinta Fujimoto (Zoologischer Anzeiger, 2024)

ZnO nanoparticles in composted sewage sludge enhance soil fertility and rice nutrition but elevate As and Pb accumulation - Luc Duc Phung; Sochan Sao; Shinta Dhewi Afriani; Arun Kumar; Toru Watanabe (Journal of Environmental Chemical Engineering, 2024)

Editing microbes to mitigate enteric methane emissions in livestock - Faheem Ahmed Khan; Azhar Ali; Di Wu; Chunjie Huang; Hamza Zulfiqar; Muhammad Ali; Bilal Ahmed; Muhammad Rizwan Yousaf; Ezi Masdia Putri; Windu Negara; Muhammad Imran; Nuruliarizki Shinta Pandupuspitasari (World Journal of Microbiology and Biotechnology, 2024)

Comparative Physiological and Transcriptomic Profiling Reveals the Characteristics of Tissue Tolerance Mechanisms in the japonica Rice Landrace Under Salt Stress - Anisa Nazera Fauzia; Mami Nampei; Kamonthip Jiadkong; Shinta; Tanee Sreewongchai; Akihiro Ueda (Journal of Plant Growth Regulation, 2024)
The aim of this study was to characterize the tissue tolerance mechanisms of rice under salt stress. Our preliminary experiment identified a japonica rice landrace Shuzenji-kokumai (SZK), which is considered to be tissue-tolerant because it can maintain better growth than salt-sensitive rice varieties while having a high-Na + concentration in the shoots under salt stress. These mechanisms differ from those of most salt-tolerant rice varieties, which have low Na + concentrations in the shoots. We compared the physiological and molecular characteristics of SZK with those of FL478, a salt-tolerant variety, and Kunishi, a salt-sensitive variety. Under salt stress conditions, SZK accumulated high levels of Na + in the roots, leaf sheaths, and leaf blades, which were almost as high as those in the salt-sensitive Kunishi. Simultaneously, SZK maintained better growth and physiological status, as determined by its higher dry weight, lower electrolyte leakage ratio, and lower malondialdehyde concentration. Expressions of OsNHX1 and OsNHX2 were upregulated in the leaf sheaths of SZK, suggesting that Na + might be compartmentalized in the vacuoles to avoid cytosolic Na + toxicity. In contrast, FL478 showed upregulation of OsHKT1;5 and OsSOS1 in the roots, which may exclude Na + from the shoots. RNA-seq analysis showed that 4623 and 1998 differentially expressed genes were detected in the leaf sheaths and leaf blades of SZK, respectively. Among them, the HSP (heat shock protein) gene expression was highly up-regulated only in SZK, indicating that SZK protects against the protein damage caused by Na + toxicity. Our findings suggest that SZK has atypical survival mechanisms under salt stress conditions. These mechanisms offer potential traits for improving salt tolerance in rice in terms of tissue tolerance.

Prevention and Treatment of Malnutrition in Older Adults Living in Long-Term Care or the Community: An Evidence-Based Nutrition Practice Guideline - Emily Riddle; Nancy Munoz; Krista Clark; Nancy Collins; Anne Coltman; Lamia Nasrallah; Shinta Nishioka; Terese Scollard; Judy R. Simon; Lisa Moloney (Journal of the Academy of Nutrition and Dietetics, 2024)

Future in the past: paternal reprogramming of offspring phenotype and the epigenetic mechanisms - Di Wu; Kejia Zhang; Kaifeng Guan; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Windu Negara; Fei Sun; Chunjie Huang (Archives of Toxicology, 2024)

Analysis of the relationship between innovative leadership and market orientation on the sustainability of technopreneurship: the mediating role of external regulatory compliance: an empirical evidence in Indonesia - Heri Sapari Kahpi; Septantri Shinta Wulandari; Anna Sofia Atichasari; Asep Marfu (Environment, Development and Sustainability, 2024)

Tocotrienol monomers and dimers from the roots of Litchi chinensis with tyrosinase inhibition activity - Awat Wisetsai; Siwattra Choodej; Dina Nur Shinta; Sarawut Tontapha; Vittaya Amornkitbamrung; Paratchata Batsomboon; Khanitha Pudhom (Phytochemistry, 2024)

Retinoic acid signaling in development and differentiation commitment and its regulatory topology - Di Wu; Faheem Ahmed Khan; Kejia Zhang; Nuruliarizki Shinta Pandupuspitasari; Windu Negara; Kaifeng Guan; Fei Sun; Chunjie Huang (Chemico-Biological Interactions, 2024)

Rb-Ni/Al2O3 as dual functional material for continuous CO2 capture and selective hydrogenation to CO - Lingcong Li; Ningqiang Zhang; Ziyang Wu; Shinta Miyazaki; Takashi Toyao; Zen Maeno; Ken-ichi Shimizu (Chemical Engineering Journal, 2023)

Comparative toxicity assessment of individual, binary and ternary mixtures of SiO2, Fe3O4, and ZnO nanoparticles in freshwater microalgae, Scenedesmus obliquus: Exploring the role of dissolved ions - Soupam Das; Sayani Giri; Shinta Ann Jose; Mrudula Pulimi; Shalini Anand; N. Chandrasekaran; Pramod Kumar Rai; Amitava Mukherjee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Effects of CuO nanoparticles in composted sewage sludge on rice-soil systems and their potential human health risks - Luc Duc Phung; Shinta Dhewi Afriani; Putri Aditya Padma Pertiwi; Hiroaki Ito; Arun Kumar; Toru Watanabe (Chemosphere, 2023)

Recent advances in chromosome capture techniques unraveling 3D genome architecture in germ cells, health, and disease - Nuruliarizki Shinta Pandupuspitasari; Faheem Ahmed Khan; Chunjie Huang; Azhar Ali; Muhammad Rizwan Yousaf; Farwa Shakeel; Ezi Masdia Putri; Windu Negara; Anis Muktiani; Bambang Waluyo Hadi Eko Prasetiyono; Limbang Kustiawan; Dimar Sari Wahyuni (Functional & Integrative Genomics, 2023)

Water sorption and glass-to-rubber transition of amorphous sugar matrices, vacuum foam- and spray-dried from alcohols - Koji Takeda; Shinta Miyazaki; Takashi Okamoto; Hiroyuki Imanaka; Naoyuki Ishida; Koreyoshi Imamura (Journal of Food Engineering, 2023)

Heterologous production of new lanthipeptides hazakensins A and B using a cryptic gene cluster of the thermophilic bacterium Thermosporothrix hazakensis - Issara Kaweewan; Shinta Ijichi; Hiroyuki Nakagawa; Shinya Kodani (World Journal of Microbiology and Biotechnology, 2023)

A new genus and species of Loricifera (Nanaloricida: Pliciloricidae) from the deep waters of Japan - Shinta Fujimoto; Hiroshi Yamasaki; Taeko Kimura; Susumu Ohtsuka; Reinhardt Møbjerg Kristensen (Marine Biodiversity, 2020)

Identification of the genes controlling biofilm formation in the plant commensal Pseudomonas protegens Pf-5 - Akihiro Ueda; Shinta Ogasawara; Keishi Horiuchi (Archives of Microbiology, 2020)

Marine tardigrades from Lützow-Holm Bay, East Antarctica with the description of a new species - Shinta Fujimoto; Atsushi C. Suzuki; Masato Ito; Takeshi Tamura; Megumu Tsujimoto (Polar Biology, 2020)

A new genus and species of Stygarctidae (Heterotardigrada: Arthrotardigrada) from Yaku-Shin-Sone bank (Northwest Pacific) - Shinta Fujimoto; Susumu Ohtsuka (Marine Biodiversity, 2019)

Pharmacological effects of TAK-828F: an orally available RORγt inverse agonist, in mouse colitis model and human blood cells of inflammatory bowel disease - Keiko Igaki; Yoshiki Nakamura; Masayuki Tanaka; Shinta Mizuno; Yusuke Yoshimatsu; Yusaku Komoike; Keiko Uga; Akira Shibata; Hisashi Imaichi; Satou Takayuki; Yoshimasa Ishimura; Masashi Yamasaki; et al. (Inflammation Research, 2019)

Epigenetic regulation of T helper cells and intestinal pathogenicity - Yuya Hagihara; Yusuke Yoshimatsu; Yohei Mikami; Yoshiaki Takada; Shinta Mizuno; Takanori Kanai (Seminars in Immunopathology, 2019)

Sedimentation limits the erosion rate of a bioeroding sponge - Joseph Marlow; David Smith; Shinta Werorilang; James Bell (Marine Ecology, 2018)
Coral reefs are increasingly threatened by anthropogenic disturbances and consequently coral cover and complexity are declining globally. However, bioeroding sponges, which are the principal agents of internal bioerosion on many coral reefs, are increasing in abundance on some degraded reefs, tipping them towards net carbonate erosion. The aim of this study was to identify the environmental factors that drive the erosion rates of the common Indonesian bioeroding sponge Spheciospongia cf. vagabunda . Sponge explants were attached to limestone blocks and deployed across seven sites characterized by different environmental conditions in the UNESCO Wakatobi Biosphere Reserve in Indonesia. Average bioerosion rates were 12.0 kg m −2 sponge tissue year −1 (±0.87 SE ), and were negatively correlated with depth of settled sediment ( r = −.717, p r = .485, p = .012). Our results suggest that although bioeroding sponges may generally benefit from coral reef degradation, bioerosion rates may be reduced on reefs that are impacted by high sedimentation, which is a common regional stressor in the South‐East Asian Indo‐Pacific.

A molecular approach to arthrotardigrade phylogeny (Heterotardigrada, Tardigrada) - Shinta Fujimoto; Aslak Jørgensen; Jesper G. Hansen (Zoologica Scripta, 2017)
The marine order Arthrotardigrada (class Heterotardigrada, phylum Tardigrada) is known for its conspicuously high morphological diversity and has been traditionally recognized as the most ancestral group within the phylum. Despite its potential importance in understanding the evolution of the phylum, the phylogenetic relationships of Arthrotardigrada have not been clarified. This study conducted molecular phylogenetic analyses of the order encompassing all families except Neoarctidae using nuclear 18S and 28S rRNA fragments. Data from two rare families, Coronarctidae and Renaudarctidae, were included for the first time. The analyses confirmed the monophyly of Heterotardigrada and inferred Coronarctidae as the sister group to all other heterotardigrade taxa. Furthermore, the results support a monophyletic Renaudarctidae + Stygarctidae clade, which has been previously suggested on morphology. Our data indicated that two subfamilies currently placed in Halechiniscidae are only distantly related to this family. We propose that these taxa are each elevated to family level (Styraconyxidae (new rank) and Tanarctidae (new rank)). The morphology of tardigrades is discussed in the context of the inferred phylogeny.

A new genus and species of Renaudarctidae (Heterotardigrada: Arthrotardigrada) from Ryukyu Archipelago, Japan - Shinta Fujimoto; Hiroshi Yamasaki (Marine Biology Research, 2017)

Seasonal variations in the stable oxygen isotope ratio of wood cellulose reveal annual rings of trees in a Central Amazon terra firme forest - Shinta Ohashi; Flávia M. Durgante; Akira Kagawa; Takuya Kajimoto; Susan E. Trumbore; Xiaomei Xu; Moriyoshi Ishizuka; Niro Higuchi (Oecologia, 2016)

Recent developments in therapeutic protein expression technologies in plants - Shah Fahad; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Muhammad Mahmood Ahmed; Yu Cai Liao; Muhammad Tahir Waheed; Muhammad Sameeullah; Darkhshan; Saddam Hussain; Shah Saud; Shah Hassan; Amanullah Jan; et al. (Biotechnology Letters, 2015)

Vessel feature changes as a tool for detecting annual rings in tropical trees - Shinta Ohashi; Naoki Okada; Amir Affan Abdul Azim; Somkid Siripatanadilok; Teera Veenin; Ahmad Zuhaidi Yahya; Tadashi Nobuchi (Trees, 2014)

Detecting invisible growth rings of trees in seasonally dry forests in Thailand: isotopic and wood anatomical approaches - Shinta Ohashi; Naoki Okada; Tadashi Nobuchi; Somkid Siripatanadilok; Teera Veenin (Trees, 2009)